Programmed Cell Death Alterations Mediated by Synthetic Indole Chalcone Resulted in Cell Cycle Arrest, DNA Damage, Apoptosis and Signaling Pathway Modulations in Breast Cancer Model - Radka Michalkova; Martin Kello; Zuzana Kudlickova; Maria Gazdova; Ladislav Mirossay; Gabriela Mojzisova; Jan Mojzis (MDPI AG, 2022)
Although new chemotherapy significantly increased the survival of breast cancer (BC) patients, the use of these drugs is often associated with serious toxicity. The discovery of novel anticancer agents for BC therapy is expected. This study was conducted to explore the antiproliferative effect of newly synthesized indole chalcone derivative ZK-CH-11d on human BC cell lines. MTT screening, flow cytometry, Western blot, and fluorescence microscopy were used to evaluate the mode of cell death. ZK-CH-11d significantly suppressed the proliferation of BC cells with minimal effect against non-cancer cells. This effect was associated with cell cycle arrest at the G2/M phase and apoptosis induction. Apoptosis was associated with cytochrome c release, increased activity of caspase 3 and caspase 7, PARP cleavage, reduced mitochondrial membrane potential, and activation of the DNA damage response system. Furthermore, our study demonstrated that ZK-CH-11d increased the AMPK phosphorylation with simultaneous inhibition of the PI3K/Akt/mTOR pathway indicating autophagy initiation. However, chloroquine, an autophagy inhibitor, significantly potentiated the cytotoxic effect of ZK-CH-11d in MDA-MB-231 cells indicating that autophagy is not principally involved in the antiproliferative effect of ZK-CH-11d. Taking together the results from our experiments, we assume that autophagy was activated as a defense mechanism in treated cells trying to escape from chalcone-induced harmful effects.